2019
DOI: 10.1016/s2542-5196(19)30084-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of earth observation-derived hydrometeorological variables to model and predict rotavirus infection (MAL-ED): a multisite cohort study

Abstract: Summary Background Climate change threatens to undermine recent progress in reducing global deaths from diarrhoeal disease in children. However, the scarcity of evidence about how individual environmental factors affect transmission of specific pathogens makes prediction of trends under different climate scenarios challenging. We aimed to model associations between daily estimates of a suite of hydrometeorological variables and rotavirus infection status ascertained through community-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…Considering that infectious virus persists not only on surfaces but also in aerosolization of virus-laden dust particles 26 , it is logical to deduce that viral survival in the air can be reduced by these factors, thus resulting in the decreased detection. These findings are also in agreement with previous modeling results that rotavirus transmission is enhanced when aerosols are able to linger in slow-moving air and inhibited by stronger winds that transport particles away from susceptible individuals 27 .…”
Section: Discussionsupporting
confidence: 93%
“…Considering that infectious virus persists not only on surfaces but also in aerosolization of virus-laden dust particles 26 , it is logical to deduce that viral survival in the air can be reduced by these factors, thus resulting in the decreased detection. These findings are also in agreement with previous modeling results that rotavirus transmission is enhanced when aerosols are able to linger in slow-moving air and inhibited by stronger winds that transport particles away from susceptible individuals 27 .…”
Section: Discussionsupporting
confidence: 93%
“…A second binary dummy variable was therefore introduced corresponding to whether the subject was in the 'treatment' (Peru) or 'control' cohorts (the other seven sites) [37]. To adjust for background cyclical trends due to disease seasonality, terms for the interactions between annual and biannual Fourier-series sine and cosine functions terms and indicator variables for the eight sites were included in the model with the terms for the main effect omitted, thus allowing for up to two annual peaks and differences in their site-specific timing and magnitude [39,40]. In addition, the non-linear effect of age was modeled using linear, quadratic and cubic terms for the child's age in continuous months.…”
Section: Exposure Variablesmentioning
confidence: 99%
“…As rotavirus cases are reduced through widespread vaccination, the overall positive association between temperature and diarrhea could strengthen, as cases of rotavirus diarrhea may be averted during cooler periods. Other studies have demonstrated rotavirus vaccination shifting or diminishing the seasonality of rotavirus infections [ 24 26 ] and that the association between meteorologic factors and rotavirus infections varies between settings with and without ongoing rotavirus vaccination [ 27 ].…”
Section: Introductionmentioning
confidence: 99%